Pengembangan Desain Pembelajaran BIPA Darmasiswa pada Pembelajar Tingkat Mahir Rendah - Prayitno Tri Laksono (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2020)
The Indonesian learning design of Indonesian for Speakers of Other Language (ISOL) has unique characteristics. This depends on the level of the learner's initial language abilities, age, national origin, learning style, learning goals, and educational background of the learner. One learning design that has its own characteristics is that at a advanced low level it has different characteristics from learners at the level below. Characteristics of advanced low level learners already have sufficiently established language skills. To be able to improve their abilities, teachers must be able to design learning that can develop their Indonesian language skills like native speakers. This research was conducted in the Darmasiswa class at Malang Islamic University in 2019/2020. The learning design used is the ASSURE model, which is a learning design using an approach to classroom orientation.